2017
DOI: 10.1186/s12943-017-0696-6
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic long noncoding RNA landscape in breast cancer

Abstract: BackgroundFew long noncoding RNAs (lncRNAs) that act as oncogenic genes in breast cancer have been identified.MethodsOncogenic lncRNAs associated with tumourigenesis and worse survival outcomes were examined and validated in Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA), respectively. Then, the potential biological functions and expression regulation of these lncRNAs were studied via bioinformatics and genome data analysis. Moreover, progressive breast cancer subtype-specific lncRNAs were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
203
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(212 citation statements)
references
References 62 publications
9
203
0
Order By: Relevance
“…Unlike messenger RNA, lncRNA does not translate into protein products, but instead function via regulation of gene transcription, posttranscriptional regulation of proteins, or epigenetic regulation of chromatin. 6 These results suggest targeting lncRNA for breast cancer diagnosis and treatment could be a promising direction. To date, dozens lncRNAs were found to be dysregulated in human breast cancer, including HOTAIR, 3 NKILA, 4 and MALAT1.…”
Section: Introductionmentioning
confidence: 93%
“…Unlike messenger RNA, lncRNA does not translate into protein products, but instead function via regulation of gene transcription, posttranscriptional regulation of proteins, or epigenetic regulation of chromatin. 6 These results suggest targeting lncRNA for breast cancer diagnosis and treatment could be a promising direction. To date, dozens lncRNAs were found to be dysregulated in human breast cancer, including HOTAIR, 3 NKILA, 4 and MALAT1.…”
Section: Introductionmentioning
confidence: 93%
“…12 lncRNA Yaoyao Guan and Adheesh Bhandari equally contributed to this study. 10,11,18 FOXD3 promoter-associated antisense lncRNA, known as linc1623 in mice, interacts with miR-150, restricting its capability to promoting oxidative stress-induced cell growth that leads to lung epithelial cell death. Downregulation of lncRNA GAS5 causes trastuzumab resistance in breast cancer.…”
Section: Foxd3mentioning
confidence: 99%
“…Previous genome-wide screening studies using lncRNA datasets from GEO and TCGA in lung cancer [55,56], gastric cancer [44] and breast cancer [57,58] also identified cell cycle-related lncRNAs. Several studies reported that dysregulation of specific lncRNAs in HCC cell lines caused cell cycle arrest and induced apoptosis, and affected the prognosis of HCC [59,60].…”
Section: Discussionmentioning
confidence: 90%